Strategies to manage hepatitis C virus infection disease burden—Volume 4. (4th November 2017) - Chen, D. S.; Hamoudi, W.; Mustapha, B.; Layden, J.; Nersesov, A.; Reic, T.; Garcia, V.; Rios, C.; Mateva, L.; Njoya, O.; Al‐Busafi, S. A.; Abdelmageed, M. K.; et al.
Summary: The hepatitis C virus (HCV) epidemic was forecasted through 2030 for 17 countries in Africa, Asia, Europe, Latin America and the Middle East, and interventions for achieving the Global Health Sector Strategy on viral hepatitis targets—"WHO Targets" (65% reduction in HCV‐related deaths, 90% reduction in new infections and 90% of infections diagnosed by 2030) were considered. Scaling up treatment and diagnosis rates over time would be required to achieve these targets in all but one country, even with the introduction of high SVR therapies. The scenarios developed to achieve the WHO Targets in all countries studied assumed the implementation of national policies to prevent new infections and to diagnose current infections through screening.